Architectural classics of the future - Shvidkovsky, Dmitry; Revzina, Yulia (project baikal, 2025)
The article is devoted to the history of classical architectural tradition, which is considered as a development path of the meanings of anthropogenic space from the prehistoric era to the present day and as a basis for further transformation of the so-called sustainable architecture. It is shown that the connection with nature, human perceptions of the world and its evolution was originally at the root of those architectural works that we consider classical today. They remain the most important properties of construction art today, and thanks to them the classics have a future.
Keywords: classics; neoclassicism; modernism; postmodernism; world and Russian architecture; prospects of classical culture